Ekspresi Protein Sitoplasmik SOCs2 pada Adenokarsinoma Kolorektal: Studi Imunohistokimia - Azmal, Nita Afriani; Intan, Shinta Ayu; Tofrizal, Tofrizal (Jurnal Kesehatan Andalas, 2022)
Inflammatory cytokines have a role in triggering cell signals in colorectal cancer. They increase signaling pathways into cells via the Janus kinase pathway (JAK) - signal transducer and activator of transcription (STAT) -suppressor of cytokine signaling (SOCs) JAK-STAT. SOCs2 protein is a cytoplasmic protein that can inhibit activation of JAK-STAT pathway so that it prevents cascade of signals into the nucleus. This protein is thought to have decreased in adenocarcinoma colorectal. Objectives: To reveal the expression of SOCs2 protein in 37 paraffin block samples in Anatomy Pathology Department Medical Faculty Andalas University. Methods: Data were taken from medical records and histopathology was assessed by HE. SOCs2 expression was evaluated by immunohistochemistry using SOCs2 polyclonal antibody (bs-1896R). Cytoplasmic expression was counted using Image J software. Results: The average of age was 56.57 years, 21 samples (55.8%) were male, depth of invasion was mostly in the tunica muscularis (T3), and 7 cases of malignancy (18.9%) were poorly differentiated. SOCs2 expression was  5 cases (13.5%).   Conclusion: There was SOCs2 expression in a small proportion of colorectal adenocarcinoma.Keywords:  SOCs2 protein, cytoplasmic inhibitor, JAK-STAT, cell signaling